Analisis Cluster Kondisi Keterampilan, Akses dan Fasilitas Teknologi Informasi dan Komunikasi di Indonesia - watin, Rahma; Permatasari, Noverlina Putri; Wijayanto, Arie Wahyu; Marsisno, Waris (Computer Engineering Departement, Universitas Komputer Indonesia, 2024)
In facing the digital transformation era, there are still imbalances in terms of skills, access, and information and communication technology facilities in Indonesia. It is necessary to group areas to identify areas that are still lagging, as evaluation material for equitable development. The clustering of regions is done by comparing the Partitioning and Hierarchical Clustering Methods. The Partitioning Clustering algorithm used is K-Means Clustering, with an optimum number of clusters of 4. The Hierarchical Clustering algorithm used is Agglomerative Ward, with a coefficient value of 0.864. Grouping using the Agglomerative Ward method produces an optimum number of clusters of 3. The Hierarchical Clustering method is better than the Partitioning method, with a Silhouette Value of 0.37.